The Role-Playing Problem-Posing Learning to Improve Students' Emotional Intelligence and Mathematics Problem-Solving Skills - Diyanti Jati Pratiwi; Tatag Yuli Eko Siswono; Neni Mariana (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
The research is aimed to observe the effect of role-playing problem-posing learning methods on emotional intelligence and mathematic problem-solving ability. This research was a quasi-experimental research with a non-equivalent pretest-posttest control group design. The sample was chosen by random sampling with Primary 4A 17 students as a control group class and Primary IV B 17 students as an experiment group class. The Data collection techniques was done through emotional intelligent questionnaire and mathematics problem-solving test. T-test was used as an analysis technique due to data collection before and after the research program. Based on T-test analysis for emotional intelligence and mathematic problem-solving ability, the data showed there was no difference before and after research in both control and experiment class with the value of sig. 2 tailed 0,303>0,05 for emotional intelligence and mathematic problem-solving ability got sig. 2 tailed scores 0,908>0,05. The differences shown in control and experiment classes after learning method in the research with the value of sig. 2 tailed 0,02<0,05 for emotional intelligence and mathematic problem-solving ability got sig. 2 tailed scores 0,01<0,05. In this research, the learning method was the only thing which caused differences, so the researcher concluded that there was an effect of role-playing problem posing learning method to students’ emotional intelligence and mathematics problem-solving ability